2009
DOI: 10.3892/or_00000444
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibitory activity of ethanol extracts of Chinese and Brazilian propolis in four human colon carcinoma cell lines

Abstract: Abstract. More than 300 bio-active compounds have been identified from bee propolis in various regions of the world. The objective of this study was to examine whether the ethanol extracts of Chinese and Brazilian propolis may exert anticancer activities in four human colon carcinoma cell lines, namely CaCo2, HCT116, HT29 and SW480. Propolis samples were extracted with ethanol, and the crude extracts were dissolved in dimethylsulfoxide and used for the experiments. In HCT116, HT29 and SW480 cell lines, the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…More importantly, we have herein established the first account that EEP treatment may display GC subtype specificity showing prominent suppressive efficacy against the differentiated-type. However, one caveat of this finding was that the enhanced anti-proliferative activity might be due to cell line growth capacity 17 .…”
Section: Discussionmentioning
confidence: 93%
“…More importantly, we have herein established the first account that EEP treatment may display GC subtype specificity showing prominent suppressive efficacy against the differentiated-type. However, one caveat of this finding was that the enhanced anti-proliferative activity might be due to cell line growth capacity 17 .…”
Section: Discussionmentioning
confidence: 93%
“…Some cancers develop resistance to TRAIL-mediated cell death, a process that, as revealed in several in vitro studies, can be reversed by propolis-derived compounds. Treatment of prostate and colon cancer cells with propolis and its constituents was proven to cause apoptosis via a TRAIL-dependent mechanism [ 133 , 137 ]. Szliszka et al found that propolis extracts at concentrations of 50 μg/mL significantly increased the levels of TRAIL in cervical tumor cell lines.…”
Section: Molecular Mechanisms Of Anticancer Activities Of Propolismentioning
confidence: 99%
“…A number of in vitro and in vivo studies confirm the anticancer activity of propolis or its active components against colon cancer cell lines ( Table 1 ). The extracts of Polish, Brazilian Red, New Zealand, and Serbian propolis have shown high levels of cytotoxicity on HCT-116 colon cell lines [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. Other studies demonstrated that Brazilian and Chinese propolis extracts inhibited the growth of human colon carcinoma HCT116, HT29, and SW480 cell lines, with IC50 values in the range of 4–41 μg/mL.…”
Section: Bee Products—anti-colon Cancer Potentialmentioning
confidence: 99%
“…Other studies demonstrated that Brazilian and Chinese propolis extracts inhibited the growth of human colon carcinoma HCT116, HT29, and SW480 cell lines, with IC50 values in the range of 4–41 μg/mL. Additionally, Chinese propolis extract caused a dose-dependent increase in the cellular mRNA levels of p21CIP1 and p53 in the HCT116 cell line [ 57 ]. The study by Russo et al showed that the Chilean propolis protects normal cells from oxidative and also reduces the vitality of Caco-2 colon adenocarcinoma cells through the induction of DNA damage [ 58 ].…”
Section: Bee Products—anti-colon Cancer Potentialmentioning
confidence: 99%